PCOS as a generational disease - risks to mother and children - Karolina Gendek; Anna Kozłowska; Weronika Dalmata; Ilona Gąbka; Jan Dąbrowski; Anna Korzeniowska (Kazimierz Wielki University, 2023)
INTRODUCTION: Polycystic ovary syndrome (PCOS) is the dominant endocrine and metabolic disorder in young women. The incidence has increased significantly over the years and now affects approximately 6-20% of women of childbearing age. AIM: The aim of the work is to present the current state of knowledge about PCOS, to show what complications it brings and to present the disease as a multi-generational problem. TECHNICAL CONDITION. DESCRIPTION: It is widely accepted that hyperandrogenism plays a fundamental role in the development of most of the reproductive and metabolic disorders associated with PCOS. Excess androgens have a detrimental effect on the metabolic homeostasis of women with PCOS, acting on various metabolic tissues. PCOS is associated with reduced fertility or infertility. Women should be aware of factors affecting fertility, especially the effects of obesity and age. After pregnancy, women with PCOS have a significantly increased risk of pregnancy-related complications, including gestational diabetes, high blood pressure disorders, preterm and caesarean delivery, and pre-eclampsia.The offspring of women with PCOS may have an increased risk of birth defects and hospitalization in childhood. According to the DOHaD theory, the unfavorable uterine environment caused by mothers with PCOS, consisting in changes in fetal metabolism, may increase the susceptibility of the offspring to diseases in adulthood, according to the DOHaD theory. In addition, the offspring of PCOS are prone to a range of metabolic diseases in early adulthood, which will also affect the health of their children. CONCLUSION: The effects of endocrine disorders affect women with PCOS as well as their offspring. Diet, weight maintenance, physical activity, anti-androgenic drugs and metformin are recommended to reduce symptoms in mothers and their children. Breaking the vicious circle of intergenerational transmission remains a huge challenge.